VASOPROTECTIVE EFFECT OF PHYSALIS ANGULATA L. LEAF WATER EXTRACT ON KIDNEY OF NÎ©-NITRO-L-ARGININE METHYL ESTER-INDUCED ENDOTHELIAL DYSFUNCTION RAT MODEL - Febianti, Zahrah; Permatasari, Nur; Soeharto, Setyawati (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was to investigate the effect of Physalis angulata L. leaf water extract on vascular rarefaction, oxidative stress, and inflammation on the kidney of NÏ‰-nitro-L-arginine methyl ester (L-NAME)-induced male Wistar rats. Methods: A total of 25 male Wistar rats were divided into five equal groups (normal control: 40 mg/kg/day of normal saline; L-NAME group; and treatments I, II, and III: L-NAME plus P. angulata L. leaf water extract doses 500 mg/kg/day, 1500 mg/kg/day, and 2500 mg/kg/day, respectively). Endothelial dysfunction was induced by 40 mg/kg/day L-NAME intraperitoneally. The treatment lasts for 15 days. Vascular rarefaction was indicated by the decrease in vascular density, which considered as vascular number per high-power field in hematoxylin-eosin staining preparation. Kidney oxidative stress test was performed by measuring malondialdehyde (MDA) level with thiobarbituric acid reactive substances assay. The inflammatory marker was the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-ÎºB) expression which examined using an immunohistochemical method with an antibody against p65. Results: At the dose of 500 mg/kg/day and 1500 mg/kg/day, P. angulata leaf water extract supplementation increased the vascular density, decreased the MDA level, and decreased the NF-ÎºB expression compared to the L-NAME group. Conclusion: The administration of P. angulata L. leaf water extract in particular concentration has a vasoprotective effect by preventing kidney vascular rarefaction, oxidative stress, and inflammation on L-NAME-induced male Wistar rat.